2017
DOI: 10.1155/2017/7659023
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Resveratrol Alleviates Osteoarthritis Pathology in C57BL/6J Mice Model Induced by a High-Fat Diet

Abstract: Obesity has been associated with osteoarthritis (OA) due to increased mass and metabolic factors which are independent of the biomechanical contribution to joint load. Resveratrol, a natural polyphenolic compound, exerts protective effects on OA through its anti-inflammatory property. However, the mechanism of resveratrol on obesity-related OA is unclear. To investigate the effect and possible mechanism of oral resveratrol on obesity-related OA, we fed C57BL/6J mice with a high-fat diet (HFD) for 16 weeks to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 54 publications
(52 reference statements)
3
37
0
Order By: Relevance
“…[ 65 ] Recent findings suggest that high-fat diet (HFD)-induced obesity can lead to the development of OA, whereas resveratrol may relieve OA pathology by reducing systemic inflammation and/or inhibiting TLR4 signaling in cartilage. [ 66 ] Therefore, resveratrol may be a promising treatment for obesity-related OA. For dietary structure, dietary fatty acid content plays an important role in the pathogenesis of OA after joint injury and supports the need for further study of dietary fatty acid supplements as a potential treatment for OA.…”
Section: Resultsmentioning
confidence: 99%
“…[ 65 ] Recent findings suggest that high-fat diet (HFD)-induced obesity can lead to the development of OA, whereas resveratrol may relieve OA pathology by reducing systemic inflammation and/or inhibiting TLR4 signaling in cartilage. [ 66 ] Therefore, resveratrol may be a promising treatment for obesity-related OA. For dietary structure, dietary fatty acid content plays an important role in the pathogenesis of OA after joint injury and supports the need for further study of dietary fatty acid supplements as a potential treatment for OA.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, resveratrol has demonstrated a great potential in preventing and/or slowing the breakdown of articular cartilage and extracellular matrix in the preclinical studies. 15 In human articular chondrocytes, resveratrol also offers anti-apoptotic, anti-inflammatory, and antioxidant effects. 16 , 27 Similarly, another preclinical study demonstrated the potent anabolic and anti-catabolic potential of resveratrol in human adult articular chondrocytes via the inhibition of the matrix-degrading enzyme.…”
Section: Discussionmentioning
confidence: 99%
“… 10 14 Preclinical studies provided accumulating evidence on its efficacy in ameliorating the degenerative articular damage that mostly attributed to its pleiotropic properties. 15 , 16 Moreover, many pieces of evidence have displayed resveratrol as one of the nutraceutical candidates for OA therapy in human. 17 , 18 Early reports showed that resveratrol has anti-inflammatory activity in acute and chronic phases of inflammation and that the effect was associated with its ability to modulate cyclooxygenase COX-1 and COX-2.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed in obesity-related OA in an animal model. The overall outcomes of this 2017 study indicate that high-fat diet-induced obesity could trigger the onset of OA, and resveratrol might alleviate OA pathology by decreasing systematic inflammation and/or inhibiting the TLR4 signaling pathway in cartilage, posing as a potential therapeutic approach for obesity-related OA [114]. Limagne E. et al investigated the pro-inflammatory paracrine interactions between human primary chondrocytes and macrophages following IL-1β treatment.…”
Section: Resveratrolmentioning
confidence: 99%